Thorsten B. Olesen (red.), Interdependence Versus Integration. Denmark, Scandinavia, and Western Europe, 1945-1960, Odense University Studies in History and Social Sciences, vol. 193, Odense: Odense University Press, 1995, kr. 250.00. - Amstrup, Niels (Politica, 1997)
-